2012
DOI: 10.5194/acp-12-12277-2012
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous VOCs rapidly modify particulate matter and its biological effects – Part 1: Simple VOCs and model PM

Abstract: Abstract. This is the first of a three-part study designed to demonstrate dynamic entanglements among gaseous organic compounds (VOC), particulate matter (PM), and their subsequent potential biological effects. We study these entanglements in increasingly complex VOC and PM mixtures in urban-like conditions in a large outdoor chamber. To the traditional chemical and physical characterizations of gas and PM, we added new measurements of biological effects, using cultured human lung cells as model indicators. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 47 publications
3
43
0
Order By: Relevance
“…The methods and procedures used in this Part 2 study were essentially identical to those reported in the Part 1 study (Ebersviller et al, 2012a). Thus, only brief summaries of these will be given here.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods and procedures used in this Part 2 study were essentially identical to those reported in the Part 1 study (Ebersviller et al, 2012a). Thus, only brief summaries of these will be given here.…”
Section: Methodsmentioning
confidence: 99%
“…A Varian 3800 GC with Saturn 2200 mass spectrometer (MS) was used to analyse condensed-phase samples (such as function-specific or filter samples). See (Ebersviller et al, 2012a) for more details on components and operating conditions for these systems.…”
Section: Direct Sampling Of the Chamber By Gas Chromatographymentioning
confidence: 99%
See 3 more Smart Citations